Raza sí, migra no : Chicano movement struggles for immigrant rights in San Diego - Patiño, Jimmy (Chapel Hill : The University of North Carolina Press, 2017)
"As immigration from Mexico to the United States grew through the 1970s and 1980s, the Border Patrol, police, and other state agents exerted increasing violence against ethnic Mexicans in San Diego's volatile border region. In response, many San Diego activists rallied around the leadership of the small-scale print shop owner Herman Baca in the Chicano movement to empower Mexican Americans through Chicano self-determination. The combination of increasing repression and Chicano activism gradually produced a new conception of ethnic and racial community that included both established Mexican Americans and new Mexican immigrants. Here, Jimmy Patiño narrates the rise of this Chicano/Mexicano consciousness and the dawning awareness that Mexican Americans and Mexicans would have to work together to fight border enforcement policies that subjected Latinos of all statuses to legal violence. By placing the Chicano and Latino civil rights struggle on explicitly transnational terrain, Patiño fundamentally reorients the understanding of the Chicano movement. Ultimately, Patiño tells the story of how Chicano/Mexicano politics articulated an "abolitionist" position on immigration--going beyond the agreed upon assumptions shared by liberals and conservatives alike that deportations are inherent to any solutions to the still burgeoning immigration debate"--Publisher's website.
Introduction: We gotta get on this immigration issue -- The Mexican American Left and Early Struggles Against the Deportation Regime, 1924-1968. Historical rights in the territory : struggles for Mexican immigrant rights from el Congreso to la Hermandad -- The Chicano Movement Confronts the Immigration Question, 1968-1976. He had a uniform and authority : border patrol violence, women's agency, and Chicano/Mexicano resistance -- For those families who are deported and have no place to land : building CASA Justicia -- The first time I met César Chávez, I got into an argument with him : California employer sanctions and Chicano debates over undocumented workers -- Delivering the Mexicano vote : immigration and the La Raza Unida party -- The sheriff must be obsessed with racism! : the Committee on Chicano Rights battles police violence -- A Chicano/Mexicano Movement : Power Concedes Nothing Without Demand, 1977-1986. Who's the illegal alien pilgrim? : the Carter Curtain, the KKK, and Chicano unity march -- Abolishment of the INS/Border Patrol : the Chicano National Immigration Conference and Tribunal -- Conclusion: The long walk for rights.
Includes bibliographical references (pages 313-326) and index.
Online resource (HeinOnline, viewed July 13, 2020).
eBooks on EBSCOhost
Keywords: Chicano movement -- California -- San Diego -- History -- 20th century; Noncitizens -- Mexico; Mexican Americans -- Ethnic identity -- History -- 20th century; Mexican Americans -- California -- San Diego -- History -- 20th century; United States -- Emigration and immigration -- Government policy; Illegal immigration -- Mexico; Noncitizens; Undocumented Immigrants; Chicano movement -- Californie -- San Diego -- Histoire -- 20e siècle.; Américains d'origine mexicaine -- Identité ethnique -- Histoire -- 20e siècle.; Américains d'origine mexicaine -- Californie -- San Diego -- Histoire -- 20e siècle.; Immigration clandestine -- Mexique; Immigrants clandestins; États-Unis -- Émigration et immigration -- Politique gouvernementale; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Illegal immigration; Chicano movement; Emigration and immigration -- Government policy; Noncitizens; Mexican Americans; Mexican Americans -- Ethnic identity; California -- San Diego; Mexico; United States; Noncitizens; 1900-1999; Electronic books; History